The ‘Manifest Injustice’ Clause in Article 4 of the Hague Convention on Private International Law: Applicability in International Commercial Contract Disputes - Yara M. A. Farouq (Law and Economy, 2024)
This paper critically examines the ‘manifest injustice’ clause in Article 4 of the Hague Convention on Choice of Court Agreements, focusing on its applicability in international commercial contract disputes. The clause serves as a safeguard to ensure fairness in choice of court agreements by allowing courts to set aside agreements that result in unjust outcomes for one of the parties. The paper explores various contexts in which this clause applies, such as situations involving unequal bargaining power, fraud, duress, coercion, procedural injustice, and unconscionable terms. It also discusses the significant legal challenges associated with its application, including the lack of a clear definition, variability in judicial interpretation, conflicts with the principle of party autonomy, and evidentiary burdens. The paper concludes that while the ‘manifest injustice’ clause is a critical tool for promoting fairness in international commerce, its effectiveness depends on the development of clearer guidelines and more consistent jurisprudence to harmonize its interpretation across jurisdictions, thereby enhancing its role in ensuring justice and equity in cross-border contractual relationships.